Migration Intentions, Practice Environment, and Satisfaction among Nigerian Nurses - Olatubi, Matthew Idowu; Alao, Ifeoluwa Elizabeth; Fagbenle, Mofiyinfoluwa Deborah; Ademuyiwa, Grace Oluwaranti; Faremi, Funmilola Adenike; Bello, Cecilia Bukola (Nurse Media Journal of Nursing, 2024)
Background: Nursing workforce migration is a function of the nursing practice environment and satisfaction with the general situation of their country of practice. There is a need to provide empirical data on the intent to migrate among nurses and satisfaction with the working environment in Nigeria.  Purpose: This study aimed to assess migration intention, favorability of practice environment, and level of satisfaction with the Nigerian environment among nurses in a private teaching hospital in Nigeria.Methods: This descriptive cross-sectional study recruited participants using a simple random sampling technique. In all, 124 nurses participated in the study. Data were collected using the migration intention questionnaire, nursing practice environment scale, and satisfaction with Nigeria environment questionnaire. All ethical principles were adhered to. Data were analyzed using Statistical Package for Social Sciences version 20 in terms of frequency, percentage, mean, and standard deviation.Results: An overwhelming majority (95.2%) had the intention to migrate to other countries, with 63.6% of them having already been in the migration process. Canada (34.8%) and the United Kingdom (33.9%) were the most sought-after countries. Nurse manager ability, leadership, and support scored highest on the favourability of the nursing practice environment (M=2.92, SD=0.80), while staffing and resources inadequacy had the lowest score (M=2.63, SD=0.68). Overall, 75.8% of the nurses described their practice environment as favourable. Political conflicts and wars were the most dissatisfying areas of Nigeria’s environment. Overall, the majority (61.3%) of nurses were dissatisfied with the Nigerian environment.Conclusion: The majority of the nurses participating in the study were planning to migrate to another country and were not satisfied with Nigeria’s environment. The nurses claimed that their practice environment was unfavourable. There is a need to make the nursing practice environment more favorable to the nurses.